Planning and designing a masterplan for the toga industry eduwisata in Kebuntunggul Village, Mojokerto, Indonesia - Wuwuh Asrining Puri; Rakhmad Wahyudi; M. Adik Rudiyanto; Nuril Ahmad (Journal of Rural Tourism, 2025)
Purpose - The purpose of this research is to describe the planning and design of the Toga Industry Edu-Tourism Masterplan for Kebontunggul Village, Gondang Subdistrict, Mojokerto Regency. The study aims to create a sustainable framework for long-term investment in the Toga industry, transforming the village into an educational tourism destination. Methodology/Design/Approach - The research uses a qualitative descriptive approach, consisting of several stages: data and information collection, analysis, and the preparation of design concepts. The data collection process involved in-depth interviews, focused discussions, and direct observations. Data analysis verified the parameters of the Toga tourism village with empirical facts and abstracted them to develop the masterplan concept. Finding - The study’s findings highlight the potential of Kebontunggul Village as a tourism village and Toga industry hub, focusing on its natural scenery, crops, water resources, and the Toga industry. The research provides a detailed direction for the development and regulation of the Toga industry edu-tourism masterplan, offering a framework for sustainable tourism and long-term investment. Originality/Value - This research provides a strategic approach to developing an educational tourism model for the Toga industry. It contributes to sustainable tourism development by outlining a masterplan that integrates education and industry, offering a unique framework for the growth of Toga-based tourism in the region.